Consolidated Spillover Report : Implications from the Analysis of the Systemic-5. (Policy Papers; Policy Paper, 2011)
Spillover reports explore the external effects of policies in five systemic economies based on the issues identified by partners. Without reprising all the results and nuances, this paper draws some overarching lessons from the exercise for the global policy debate.